Endobronchial Mass: A Rare Manifestation of Multiple Solitary Plasmacytoma - Thanawat Anukanchanavera; Chayaporn Kaewsathorn Kaewsathorn; Nantaka Kiranantawat (Journal of the Belgian Society of Radiology, 2023)
Multiple solitary plasmacytoma is the rare presentation of plasma cell neoplasm that can mimic multiple metastases. Primary endobronchial plasmacytoma is an extremely rare condition of extramedullary plasmacytoma. Here, we describe a case of multiple solitary plasmacytoma that initially presented with an endobronchial mass. Teaching Point: The differential diagnosis of multiple lesions in the airway is mainly metastasis and multiple solitary plasmacytoma.